1999
DOI: 10.1093/protein/12.6.439
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human serum albumin at 2.5 Å resolution

Abstract: A new triclinic crystal form of human serum albumin (HSA), derived either from pool plasma (pHSA) or from a Pichia pastoris expression system (rHSA), was obtained from polyethylene glycol 4000 solution. Three-dimensional structures of pHSA and rHSA were determined at 2.5 A resolution from the new triclinic crystal form by molecular replacement, using atomic coordinates derived from a multiple isomorphous replacement work with a known tetragonal crystal form. The structures of pHSA and rHSA are virtually identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
1,243
0
18

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,641 publications
(1,335 citation statements)
references
References 23 publications
43
1,243
0
18
Order By: Relevance
“…Terminal regions of sequential domains contribute to the formation of interdomain h10-h1 helices linking subdomain IB to subdomain IIA and subdomain IIB to subdomain IIIA, respectively ( Fig. 1) [2,3,[10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Terminal regions of sequential domains contribute to the formation of interdomain h10-h1 helices linking subdomain IB to subdomain IIA and subdomain IIB to subdomain IIIA, respectively ( Fig. 1) [2,3,[10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Each domain contains 10 helices and is divided into anti-parallel six-helix and four-helix subdomains (A and B). 7 The X-ray structural studies showed that these two primary drug sites (Sudlow's site I and II) 8,9 are located in the subdomain IIA and subdomain IIIA, respectively. 10 We and others have shown that Sudlow site I at subdomain IIA is a large binding pocket and can be further divided into three non-overlapping subsites.…”
Section: Introductionmentioning
confidence: 99%
“…The albumin‐binding activity of ABP‐HBVC was further monitored through time‐course dynamic light scattering (DLS) analysis after ABP‐HBVC (or ABP‐free HBVC) was added to human serum (Figure 2B,C). The particle size of ABP‐free HBVC (indicated by blue dotted circles in Figure 2B) never changed for 24 h in human serum, while both of the DLS peaks for ABP‐HBVC and HSA (that are present as a dimer having the size of ≈14 nm,24, 25 indicated by red dotted circles in Figure 2C) disappeared, and the new peaks around 50 nm (indicated by red arrows in Figure 2C) newly appeared immediately after ABP‐HBVC was added to human serum, showing clearly the binding between ABP‐HBVC and serum albumins. We also measured the amount of E. coli ‐derived endotoxin (LPS) involved in the purified ABP‐HBVC and ABP‐free HBVC.…”
Section: Resultsmentioning
confidence: 99%